Identification of Visual Attentional Regions of the Temporoparietal Junction in Individual Subjects using a Vivid, Novel Oddball Paradigm - Devaney, Kathryn J.; Rosen, Maya L.; Levin, Emily J.; Somers, David C. (Frontiers in Human Neuroscience, 2019)
The Temporoparietal Junction (TPJ) of the cerebral cortex is a functionally heterogeneous region that also exhibits substantial anatomical variability across individuals. As a result, the precise functional organization of TPJ remains controversial. One or more regions within TPJ support visual attention processes, but the ‘attention TPJ’ is difficult to functionally observe in individual subjects, and thus is typically identified by averaging across a large group of subjects. However, group-averaging also blurs localization and can obscure functional organization. Here, we develop and test an individual-subject approach to identifying attentional TPJ. This paradigm employs novel oddball images with strong visual drive to produce robust TPJ responses in individuals. Vivid, novel oddballs drive responses in two TPJ regions bilaterally, a posterior region centered in posterior Superior Temporal Sulcus (TPJ-sts) and an anterior region in ventral Supramarginal Gyrus (TPJ-smg). Although an attentional reorienting task fails to drive TPJ activation in individuals, group analysis of the attentional reorienting contrast reveals recruitment of right TPJ-sts, but not right TPJ-smg. Similarly, right TPJ-sts, as identified in individual subjects by the vivid, novel oddball contrast, is activated by attentional reorienting, but right TPJ-smg is not. These findings advance an individual-subject based approach to understanding the functional organization of TPJ.